New application of sine-cosine method for the generalized (2+1)-dimensional nonlinear evolution equations - Najafi, Malihe; Arbabi, Somayeh; Najafi, Mohammad (International Journal of Advanced Mathematical Sciences, 2013)
By means of the idea of sine-cosine method, some analytic solutions for the generalized (2+1)-dimensional nonlinear evolution equations are presented. (2+1)-dimensional breaking soliton equation and (2+1)-dimensional Calogero Bogoyavlenskii-Schi? (CBS) equation and (2+1)-dimensional Bogoyavlenskii’s Breaking soliton equation are chosen to illustrate the e?ectiveness of the method.